Omicron SARS-CoV-2 infection management and outcomes in patients with hematologic disease and recipients of cell therapy - Piñana, José Luis; Vazquez, Lourdes; Heras, Inmaculada; Aiello, Tommaso Francesco; López-Corral, Lucia; Arroyo, Ignacio; Soler-Espejo, Eva; García-Cadenas, Irene; Garcia-Gutierrez, Valentín; Aroca, Cristina; Chorao, Pedro; Olave, María T.; et al. (Frontiers in Oncology, 2024)
Introduction: Scarce real-life data exists for COVID-19 management in hematologic disease (HD) patients in the Omicron era.Purpose: To assess the current clinical management and outcome of SARS-CoV-2 infection diagnosed, identify the risk factors for severe outcomes according to the HD characteristics and cell therapy procedures in a real-world setting.Methods: A retrospective observational registry led by the Spanish Transplant Group (GETH-TC) with 692 consecutive patients with HD from December 2021 to May 2023 was analyzed.Results: Nearly one-third of patients (31%) remained untreated and presented low COVID-19related mortality (0.9%). Nirmatrelvir/ritonavir was used mainly in mild COVID-19 cases in the outpatient setting (32%) with a low mortality (1%), while treatment with remdesivir was preferentially administered in moderate-to-severe SARS-CoV-2 infection cases during hospitalization (35%) with a mortality rate of 8.6%. The hospital admission rate was 23%, while 18% developed pneumonia. COVID-19-related mortality in admitted patients was 14%. Older age, autologous hematopoietic stem cell transplantation (SCT), chimeric antigen receptor T-cell therapy, corticosteroids and incomplete vaccination were factors independently associated with COVID-19 severity and significantly related with higher rates of hospital admission and pneumonia. Incomplete vaccination status, treatment with prior anti-CD20 monoclonal antibodies, and comorbid cardiomyopathy were identified as independent risk factors for COVID-19 mortality.The results support that, albeit to a lower extent, COVID-19 in the Omicron era remains a significant problem in HD patients. Complete vaccination (3 doses) should be prioritized in these immunocompromised patients. The identified risk factors may help to improve COVID-19 management to decrease the rate of severe disease, ICU admissions and mortality.